2013
DOI: 10.5037/jomr.2013.4302
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on Absorbed Dose Distribution in Intraoral X-ray Imaging When Using Tube Voltages of 60 and 70 kV for Bitewing Imaging

Abstract: ObjectivesEfforts are made in radiographic examinations to obtain the best image quality with the lowest possible absorbed dose to the patient. In dental radiography, the absorbed dose to patients is very low, but exposures are relatively frequent. It has been suggested that frequent low-dose exposures can pose a risk for development of future cancer. It has previously been reported that there was no significant difference in the diagnostic accuracy of approximal carious lesions in radiographs obtained using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…energy dependence, and adequate accuracy. [9][10][11] Gafchromic film is a self-developing film and has a radiosensitive layer that contains a crystalline diacetylene monomer, which, when irradiated, polymerizes and darkens. 12 The amount of darkening is related to the absorbed dose.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…energy dependence, and adequate accuracy. [9][10][11] Gafchromic film is a self-developing film and has a radiosensitive layer that contains a crystalline diacetylene monomer, which, when irradiated, polymerizes and darkens. 12 The amount of darkening is related to the absorbed dose.…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
“…12 The film was exposed to 8 doses of radiation between 2000 and 110,000 mGy; 1 nonirradiated film was used for calculating the background value. In a previous study, 11 the film was calibrated for kilovolt (kV) settings from 60 to 120 kV by using the same ionization chamber (which has a flat energy response in this interval). It was found that the calibration curves coincided.…”
Section: Phantoms and Gafchromic Filmsmentioning
confidence: 99%
“…Dosimetric film has been suggested as a more accurate alternative for these modalities. 19,20 As far as we know, no study has determined the dose to child patients from all X-ray modalities of interest when specifically diagnosing an impacted canine. The current study aims to determine and compare the dose from both periapical and panoramic radiographs as well as CBCT examinations for children having impacted canines with possible root resorption in neighbouring teeth, using TLD and film measurements.…”
mentioning
confidence: 99%
“…5 To improve the technique of bitewing radiography and also make it more popular, scientists are trying to minimize the radiation risk connected to its usage. It has been proven recently that lowering the peak voltage of the intraoral X-ray tube from 70 kV to 60 kV has no negative effects on the quality of the picture and, indirectly, on the follow-up of carious lesions 17,18 . It has also been proven that removal of soft tissues (especially the cheek) from the area where the X-ray beam is directed improves the quality of the X-ray of the bone and the contrast of the picture, thereby it increases the sensitivity of a bitewing.…”
Section: Discussionmentioning
confidence: 99%